The Effect of Free Cash Flow, Liquidity and Company Growth on Debt Policy and Profitability as Moderating Variables in Mining Sector Companies Listed on the Indonesia Stock Exchange for the 2017-2021 Period - Nita Nella Thalia Harahap; Kersna Minan (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine the effect of free cash flow, liquidity, and company growth on debt policy with profitability moderating the independent variables in mining sector companies listed on the Indonesian stock exchange in 2017-2021. Debt policy is very important for managers in companies that are expanding. The total population of this study is 49 companies and the sample in this study was 19 companies x 5 years of research 95 observations. The analytical technique used in this research is descriptive test, classic assumption test which consists of normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test, multiple linear regression test and moderated regression analysis (MRA). The results showed that the free cash flow has no effect on debt policy, liquidity has an effect on debt policy, company growth has no effect on debt policy, in mining sector companies listed on the Indonesian stock exchange for the 2017-2021 period. Meanwhile, for the Moderated Regression Analysis (MRA) test, the results show that profitability does not moderate the effect of free cash flow on debt policy, profitability does not moderate the effect of liquidity on debt policy, and profitability does not moderate the effect of company growth on debt policy in companies listed on the Indonesian stock exchange for the period 2017-2021.